One-pot superhydrophilic surface modification of waste polyurethane foams for high-efficiency oil/water separation. (1st August 2022) - Ao, Chenghong; Jiang, Lichao; Wang, Qunhao; Xue, Xiaolin; Gai, Jinggang; Zhang, Wei; Lu, Canhui
Abstract: Despite of the fact that polymers have brought tremendous convenience to human life, they have also inevitably caused considerable environmental pollution after their service life. Therefore, a feasible strategy that can effectively recycle waste polymers and endow them with high added value is much desired. Superwetting materials have shown great promise in oily wastewater treatment because of their high oil/water separation efficiency. However, most of these materials present some limitations, such as complex preparation procedures and poor salt tolerance, which hamper their practical applications. In this study, an iron hydroxide@polydopamine@waste polyurethane foam (Fe(OH)3 @PDA@WPU) was synthesized via a facile and mild "one-pot" reaction. During this process, polymerization of dopamine and in situ growth of Fe(OH)3 were simultaneously realized, and the resultant PDA and Fe(OH)3 nanoparticles were firmly attached to the surface of WPU. Due to the abundant hydrophilic groups from PDA and Fe(OH)3 coupled with the surface roughness created by Fe(OH)3 nanoparticles, the surface properties of the foam could be changed from hydrophobic to superhydrophilic. Remarkably, the Fe(OH)3 @PDA@WPU was capable of separating various oil/water mixtures even under some severe conditions (e.g. erosion in a saturated sodium chloride solution and longtime sonication), demonstrating high potential in marine oily sewage treatment. Moreover, this work also paved a new path for reducing the negative impact of waste polymer foams on our environment, and in the meantime realizing their high value utilization. Graphical abstract: Image 1 Highlights: A superhydrophilic foam is prepared by a facile and massively scalable method. High surface energy and micro-nano surface roughness are realized simultaneously. The foam presents ultrahigh water flux and excellent recyclability. The foam possesses outstanding salt resistance and mechanical stability. A feasible route for high-value utilization of WPU is verified.